Evolution of the Concept of Interoperability of Open Information Systems - S. Yu. Mikhnevich; A. A. Tsezhar (Цифровая трансформация)
The article compares the deﬁnitions of interoperability presented in international standards and documents. The transformation of this concept is shown and justiﬁed, starting with a technical deﬁnition and ending with a complex concept, which is an integral element of digital transformation processes. The main processes (business management, consumer management, communication channel management and service-oriented technology management) necessary for the implementation of the New European Interoperability Strategy are presented. The principles and levels (political, legislative, organizational, semantic and technical) of interoperability are presented. The experience of the United States of America, the countries of Europe and the Russian Federation on the regulatory consolidation of the interoperability of open information systems and the practice of its use in some areas of activity are analyzed. A model of interoperability is presented in accordance with the standards of the Russian Federation, including technical, semantic and organizational levels. On the basis of the analysis carried out, a more complete normative consolidation of this concept in the Republic of Belarus is proposed.